2021
DOI: 10.1007/s43630-021-00063-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the pH-dependence of the oxidation of FAD in VcCRY-1, a member of the cryptochrome-DASH family

Abstract: Vibrio cholerae cryptochrome-1 (VcCRY-1) is a member of the cryptochrome DASH family. The flavoprotein appears to use blue light both for repair of cyclobutane pyrimidine dimers (CPDs) on DNA and signal transduction. Earlier, we found that it was almost impossible to oxidize the FADH• state upon binding to a CPD, and, in the absence of substrate, the rate of FADH• oxidation was much larger at high pH (Gindt et al. in Biochemistry 54:2802-2805. Here, we present the pH-dependence of the oxidation of FADH• by fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…We are happy to announce that today, this virtual volume unites 18 contributions by scientists from 17 countries (Canada, Czech republic, Finland, France, Germany, Hungary, India, Italy, Japan, Lebanon, Poland, Russia, Spain, Switzerland, Taiwan, UK, US) touching upon the wide variety of the subjects dealt with by Klaus at various times [25,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
See 1 more Smart Citation
“…We are happy to announce that today, this virtual volume unites 18 contributions by scientists from 17 countries (Canada, Czech republic, Finland, France, Germany, Hungary, India, Italy, Japan, Lebanon, Poland, Russia, Spain, Switzerland, Taiwan, UK, US) touching upon the wide variety of the subjects dealt with by Klaus at various times [25,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
“…Gindt et al studied the oxidation of native semiquinone FADH° in VcCRY-1, a member of the cryptochrome DASH family, whose flavoproteins may use blue light both for repairing CPDs and for signal transduction [136]. The authors found both pH and substrate-binding-dependent oxidation kinetics.…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
“…In contrast, the highest sensitivity to glucose test-strips with the dried sensing layer was obtained with the gel prepared in citrate buffer (Figure 2b,c). The observed difference in enzyme activity could be explained in terms of different interaction rates between oxygen and reduced cofactor FAD/FADH2 of GOx in solution (see Reactions (1) and ( 2) and the same reactions in the presence of RedOx mediator in the gels [37]):…”
Section: Impact Of Buffer Type On Electrochemical Response Of Amperom...mentioning
confidence: 99%
“…At the high glucose concentration, the use of PPBI buffer with pH 7.4 and AcB with pH 5.5 led to a significant current decrease, especially for AS containing gels. The reason The observed difference in enzyme activity could be explained in terms of different interaction rates between oxygen and reduced cofactor FAD/FADH 2 of GOx in solution (see Reactions (1) and ( 2) and the same reactions in the presence of RedOx mediator in the gels [37]):…”
Section: Impact Of Buffer Type On Electrochemical Response Of Amperom...mentioning
confidence: 99%